Monetarists and Keynesians on Central Banking: A Study of a Failed Debate - Thomas Mayer (University of California, Department of Economics, 1996)
This paper reviews and appraises the debate about whether the central bank should pursue counter-cyclical policy or generate a stable monetary growth rate. It focuses on whether the participants have followed the rules of "good conversation," and concludes that they have not. Monetarist have over-stated their case, and their opponents have, in large part, just ignored salient points that the monetarists have raised. All the same, the debate has advanced economics to some extent. To support these conclusions the literature generated by this debate is discussed in some detail.
Keywords: 330